Proceedings of the American Catholic Philosophical Association - American Catholic Philosophical Association (Washington, D.C. : The Office)
Includes a list of members.
Description based on: Vol. 45, copyrighted in 1971.
Each vol. has also individual title.
Vol. for 1944 not published.
Became annual supplement to: American Catholic philosophical quarter ly in 1990.
SERBIB/SERLOC merged record
Keywords: American Catholic Philosophical Association -- Periodicals; Philosophy -- Periodicals. -- Congresses; Philosophy -- Congresses. -- Congresses; Catholic Church and philosophy -- Congresses